Hydrogen storage properties of nanoconfined LiBH4–Ca(BH4)2 - Javadian, Payam; Sheppard, Drew; Buckley, Craig; Jensen, T. (ELSEVIER, 2015)
The hydrogen storage properties of the eutectic melting metal borohydrides, 0.7LiBH4–0.3Ca(BH4)2, nanoconfined in two carbon aerogel scaffolds with different surface areas and pore volumes (pristine and CO2-activated) are presented and compared to the bulk properties. The temperature of hydrogen release investigated by temperature programmed desorption mass spectroscopy is reduced by 83 °C for nanoconfined LiBH4–Ca(BH4)2 in the pristine scaffold and by 95 °C in the CO2-activated scaffold, compared to that of the bulk. This corresponds to apparent activation energies, EA, of 204, 156 and 130 kJ/mol. Several cycles of reversible, continuous release and uptake of hydrogen is investigated by the Sieverts' method. Nanoconfined LiBH4–Ca(BH4)2 in the CO2-activated scaffolds demonstrate high degree of stability, releasing 80% and 73% of the original hydrogen content in the second and third hydrogen release cycle, respectively. However most importantly, this study shows that CO2-activated carbon aerogel, CA-6, is more stabile against reaction with the metal hydride and a lower amount of borates and oxides are formed during melt infiltration and hydrogen release and uptake cycling. We conclude that the CO2-activated scaffold is more inert, provides faster kinetics and higher stability over several cycles of hydrogen release and uptake and has the potential to provide useful hydrogen storage densities in the range ~12 wt% H2.